Decay of correlations and memory loss for Lasota–Yorke convex maps. Issue 3 (3rd July 2021) - Cui, Hongfei
Abstract : For a class of piecewise convex maps f on the interval [ 0, 1 ], we show that f has a unique absolutely continuous invariant probability measure μ with exponential decay of correlations, and we also present the explicit upper bounds on the rate. Moreover, we show the exponential loss of memory for a sequential dynamical system consisting of piecewise convex maps.